Perspective 80 : Art 11'80. - Art Basel Basel 1980 (Basel : Art Internationale Kunstmesse Basel, 1980)
D'Argenio, Ernesto ; Armleder, John ; Bechtold, Gottfried ; Bunk, Holger ; Cannavacciuolo, Maurizio ; Cragg, Tony ; De Gennaro, Tullio ; Lunanova, Paolo ; Meier, Al ; Morrel, Owen ; Nisslmüller, Manfred ; Pozarek, Vaclav ; Simoni, Mariella ; etc.
Perspective 80 : Art 11'80, Basel, 12. - 17. Juni 1980
boek